Konsep Modernisme Pendidikan Islam Dalam Qur’an Surat Al-Baqarah Ayat 151 Perspektif Kitab Tafsir Al-Manar Karya Muhammad Abduh Dan Rasyid Ridha - Amanulloh, Anis; Yusuf, Enjang Burhanudin (Peneliti.net, 2024)
Innovation of Islamic schooling in al-Manar's understanding is the restoration of Islamic training in the fields of educational program, showing staff, foundations, organization, showing strategy, guardians, society and government who team up with one another to make a more present day Islamic training with a taghrib and discourse model. There are two schools of instructive innovation, truth be told: To start with, the model of secularism (dualism) which has been executed by Western countries to accomplish instructive advancement (in view of the division of Islamic strict schooling and general training). Second, the integralistic model, specifically the presence of associations between subjects in schooling (as communicated by Fazlur Rahman). Strict schooling should be connected to general training as well as the other way around, general schooling should have a strict soul so it produces logical advancement that remaining parts in the heavenly hall. This kind of examination is library research. The technique utilized in this exploration is subjective strategy. This exploration additionally utilizes topical strategies to get the normal responses.